Adultery (Aida Macaraeg case no. 7892) - Brocka, Lino.; Mendoza, Aida Sevilla; Santos, Vilma; Salvador, Phillip; Reyes, Jose Javier; Regal Home Video (Firm). (Pasig City Regal Home Video, 2008)
Dreaming to be released from her miserable life of poverty, Aida, a waitress, abandons her bedridden father, her moralistic mother, her jobless brother and her good-for-nothing sister to live with her boyfriend Carding, who she believes will save her from her miserable life. In his desire to earn quick money, Carding gets involved with illegal drugs and is jailed. Aida is pregnant and while Carding is in jail, she has an abortion. She then marries another man. Carding is released from prison and finds out about his wife's new life. He decides to sue her for adultery.
Story, Aida Sevilla Mendoza ; screenplay, Jose Javier Reyes ; produced by Lily Yu Monteverde ; directed by Lino Brocka.
Vilma Santos; Phillip Salvador.
Keywords: Adultery -- Drama